Molecular dynamics and a spectroscopic study of sulfur dioxide absorption by an ionic liquid and its mixtures with PEO. Issue 41 (10th October 2016) - Hoher, Karina; Cardoso, Piercarlo F.; Lepre, Luiz F.; Ando, Rômulo A.; Siqueira, Leonardo J. A.
Abstract : Physical absorption of SO2 is more efficient in PEO than in a quaternary ionic liquid. Abstract : An investigation comprising experimental techniques (absorption capacity of SO2 and vibrational spectroscopy) and molecular simulations (thermodynamics, structure, and dynamics) has been performed for the polymer poly(ethylene oxide) (PEO), the ionic liquid butyltrimethylammonium bis(trifluoromethylsulfonyl)imide ([N4111 ][Tf2 N]) and their mixtures as sulfur dioxide (SO2 ) absorbing materials. The polymer PEO has higher capacity to absorb SO2 than the neat ionic liquid, whereas the mixtures presented intermediary absorption capacities. The band assigned to the symmetric stretching band of SO2 at ca. 1140 cm −1, which is considered a spectroscopic probe for the strength of SO2 interactions with its neighborhood, shifts to lower wavenumbers as more negative total interaction energy values of SO2 were evaluated from the simulations. The solvation free energy of SO2, Δ G sol, correlates linearly with the absorption capacity of SO2 . The negative values of Δ G sol are due to negative and positive values of enthalpy and entropy, respectively. In the ionic liquid, SO2 weakens the cation–anion interactions, whereas in the mixture with a high content of PEO these interactions are slightly increased. Such effects were correlated with the relative population of cisoid and transoid conformers of Tf2 N anions as revealed by Raman spectroscopy. Moreover, the presence of SO2 in the systems provokes the increase of diffusion coefficients of the absorbing species in comparison with the systems without the gas. Proper to the slow dynamics of the polymer, the diffusion coefficient of ions and SO2 diminishes with the increase of the PEO content.